Neural Stem Cell Plasticity: Advantages in Therapy for the Injured Central Nervous System - Ottoboni, Linda; Merlini, Arianna; Martino, Gianvito (Frontiers in Cell and Developmental Biology, 2017)
The physiological and pathological properties of the neural germinal stem cell niche have been well studied in the past 30 years, mainly in animals and within given limits in humans, and knowledge is available for the cyto-architectonic structure, the cellular components, the timing of development and the energetic maintenance of the niche, as well as for the therapeutic potential and the cross talk between neural and immune cells. In recent years we have gained detailed understanding of the potentiality of neural stem cells (NSCs), although we are only beginning to understand their molecular, metabolic and epigenetic profile in physiopathology and, further, more can be invested to measure quantitatively the activity of those cells, to model in vitro their therapeutic responses or to predict interactions in silico. Information in this direction has been put forward for other organs but is still limited in the complex and very less accessible context of the brain. A comprehensive understanding of the behavior of endogenous NSCs will help to tune or model them towards a desired response in order to treat complex neurodegenerative diseases. NSCs have the ability to modulate multiple cellular functions and exploiting their plasticity might make them into potent and versatile cellular drugs.